Auditoría Financiera al Gobierno Autónomo Descentralizado de la parroquia Buenavista, cantón Chaguarpamba, provincia de Loja, 01 de Enero al 31 de Diciembre del 2022. - Flores Cuenca, Jade Jazmín (2024)
The following research entitled Financial Audit of the Decentralized Autonomous Government of Buenavista Parish, Chaguarpamba Canton, Loja Province, January 1st to December 31st, 2022, focused on achieving the established objectives, which consisted of evaluating the internal control system in accordance with the legal and regulatory provisions applicable to the GAD of Buenavista Parish. In addition, we sought to determine the validity of the accounts reflected in the financial statements through the application of techniques and procedures in accordance with the audit programs. The result of this work was reflected in a final financial audit report that includes comments, conclusions and recommendations, with the purpose of contributing to the GAD's decision makers for an adequate and timely management. The execution of the procedures established in the various audit programs involved the detailed analysis and verification of each component, and the preparation of working papers in accordance with international auditing standards, which allowed the preparation of the final report describing the internal control weaknesses of the items examined. The most outstanding results, the absence segregation of duties, the lack of policies and procedures for the preservation of supporting documents for accounts payable and expenses were noted. For which it is recommended to establish procedures to review and analyze exhaustively all activities and operations carried out by the entity, in order to detect possible deficiencies or inconsistencies in the management and apply corrective measures in accordance with the legal regulations in force.